INTRAMURAL AEROMYCOLOGICAL STUDY OF RURAL HOSPITAL OF DESAIGANJ WADSA, DISTRICT GADCHIROLI MAHARASHTRA. - DHANSHRI R. BANGALKAR,; SHANKARG.KUKREJA,; ARVIND J. MUNGOLE, (The Bioscan, 2025)
The study was conducted on indoor environment of Rural hospital of Desaiganj Wadsa located in Gadchiroli district of Maharashtra state, in respect to aeromycoflora of Rural Hospital. In this study aeromycoflora were investigated from February, 2023 to January, 2024 for a year at an interval of 15 days. The sampling was conducted from the different section of hospital, such as OPD (Outpatient department), General ward and Dressing Ward. The indoor ae romycoflora was isolated by two methods with the help of Hi Air Sampler (Mark ll), Hi Media Laboratories, India and simultaneous Exposure Petri plate method. In exposure Petri plate method culture media Czapek’s Dox Agar (CDA) was utilized and Rose Bengal Strips were used in Hi Air sampler. Total 1320 colonies were appeared by Exposure Petri plate method and total 6900 CFUs/m 3 were trapped by Hi media air sampler method. The concentration of aeromycoflora in rainy season was high because of high humidity an d low temperature. Fungal spores exhibit monthly and seasonal variation. Fungal spore concentration was maximum in humid months and decreases in dry and hot months. Growth of fungi is directly proportional to the Humidity and inversely proportional to te mperature.